Aqueous organic redox-targeting flow battery based on Nernstian-potential-driven anodic redox-targeting reactions. Issue 12 (23rd February 2022) - Zhang, Hongchao; Huang, Qinghong; Xia, Xue; Shi, Yanjun; Shen, Yong-Miao; Xu, Juan; Chen, Zhidong; Cao, Jianyu
Abstract : An insoluble π-conjugated heterocyclic compound, tribenzo[ a, c, i ]phenazine-10, 15-dione, is first reported as an anodic capacity booster for aqueous organic redox-targeting flow batteries. Abstract : Aqueous organic flow batteries (AOFBs) hold great promise for large-scale energy-storage applications because of their high theoretical specific capacity, use of only earth-abundant elements, ease of large-scale manufacturing and environmental sustainability of the organic redox-active electrolyte materials. Numerous organic molecules/polymers have been explored as redox-active electrolyte materials for AOFBs. However, their low solubility in aqueous solution greatly restricts their practical application. Herein, highly efficient single-molecule redox-targeting (SMRT) reactions between a solid organic-based energy-storage material (tribenzo[ a, c, i ]phenazine-10, 15-dione, TBPDO) and two water-soluble redox shuttle molecules (anthrafravic acid and lawsone) driven by Nernstian potential are adopted to effectively circumvent the solubility limit in aqueous electrolytes, thus increasing the energy density of AOFBs. The aqueous organic redox-targeting flow battery (RTFB) employing TBPDO as an anodic capacity booster demonstrates a considerably enhanced volumetric capacity (energy density) and high material utilization (80.2%) as well as an outstanding capacity retention of 99.82% per cycle (∼98.56% per day) with high energy efficiency (80.7%) during long-term charge–discharge cycling.